Factors of Personal Hygiene Habits and Scabies Symptoms at Islamic Boarding School - Shelvi Indah Ayu Puspita; Fatma Nur Ardiati; Retno Adriyani; Neil Harris (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2021)
Background: Scabies is a contagious skin disease caused by mite Sarcoptes scabiei. The global incidence of scabies in 2014 was 0.3%-46%, while the incidence of scabies in Indonesia, especially in Banyuwangi Regency was 1871 cases in 2016 and 1730 cases in 2017. Objective: The study objective was to determine the relationship between personal hygiene and symptoms of scabies among students. Methods: This study was an observational study with a cross-sectional design located at the Salafiyah Syafi’iyah Nurul Amin Islamic Boarding School, Kalipuro, Banyuwangi. The number of students living in Islamic boarding schools was 191 students, the sample size was 63 students by simple random sampling. Data regarding personal hygiene habits were collected in April-May 2020, it used Google Forms sent via WhatsApp application to the students and in-depth interviews with the student caregivers. Data analysis using chi-square test, presented in tables and narrative. Results: The results showed that 42.9% of students had symptoms of scabies and there was a significant relationship between personal hygiene and symptoms of scabies, especially in habit of scratching (P value = 0.000) and the habit of using clothes, towels, as well as prayer tools together (P value = 0.012). Conclusion: The habit of scratching body parts with nails and using clothes, towels and, prayer tools alternately could be risk factors for the transmission of scabies to students. Students should have good personal hygiene and not share their personal equipment such as clothes, towels, and, prayer tools. The boarding school managers were advised to complete sanitation facilities, to organize a clean and tidy bedroom competition between the students.